Two new forest pathogens in Phaeolus (Polyporales, Basidiomycota) on Chinese coniferous trees were confirmed by molecular phylogeny - Yuan, Yuan; Wu, Ying-Da; Wang, Ya-Rong; Zhou, Meng; Qiu, Jun-Zhi; Li, De-Wei; Vlasák, Josef; Liu, Hong-Gao; Dai, Yu-Cheng (Frontiers in Microbiology, 2022)
Phaeolus schweinitzii (Fr.) Pat. was originally described in Europe and is considered a common forest pathogen on conifers in the Northern Hemisphere. Our molecular phylogeny based on samples from China, Europe, and North America confirms that P. schweinitzii is a species complex, including six taxa. P. schweinitzii sensu stricto has a distribution in Eurasia; the samples from Northeast and Southwest China are distantly related to P. schweinitzii sensu stricto, and two new species are described after morphological, phylogenetic, and geographical analyses. The species growing on Larix, Picea, and Pinus in Northeast China is described as Phaeolus asiae-orientalis. Another species mostly occurring on Pinus yunnanensis in Southwest China is Phaeolus yunnanensis. In addition, three taxa distributed in North America differ from P. schweinitzii sensu stricto. Phaeolus tabulaeformis (Berk.) Pat. is in Southeast North America, “P. schweinitzii-1” in Northeast North America, and “P. schweinitzii-2” in western North America.